(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Almost all hemophilia patients are treated with fresh frozen plasma and other alternatives. As they are on multiple transfusion of FFP, majority of the patient experience adverse reaction to FFP transfusion. There are various types of adverse events occur that are documented in national and international data. My research activity targeted to explore commonly encountered adverse events among Bangladeshi population. This helps the physician to plan a management protocol. Objective: The objective of the study was to evaluate the adverse events of FFP transfusion who are receiving FFP for long time. Materials and Method: It was a prospective type of observational study. The study was carried out in the Department of Transfusion Medicine, BSMMU, Dhaka, Bangladesh. This study was conducted from July 2011 to June 2012 for a period of one (1) year. 60 patients with hemophilia were selected from patients attending at day care unit of Transfusion Medicine dept. of BSMMU. Results: Among 60 patients, 53.33% patients develop itching 36.67% patients developed urticaria, 6.67% patients develops fever and rigor and 3.33 patients developed nausea. Conclusion: In this study it was found that majority of the patients developed itching following transfusion of FFP. Adverese events like urticaria, fever and nausea ranked as 2nd, 3rd and 4th position respectively. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.148-151